Republic.com / Cass Sunstein. - Sunstein, Cass R. (Princeton University Press, 2002)
This text shows us how to approach the Internet as responsible people. Democracy, it maintains, depends on shared experiences and requires people to be exposed to topics and ideas that they would not have chosen in advance.